Managing Lean Principles applicability and implementation in the mining industry in Ghana. A Review Paper on Related Literature. - Ofori-Okyere, Isaac; Atanga, Renas Ayebono; Okine, Bernard Adjetey (Archives of Business Research, 2016)
This paper reviewed both theoretical and empirical literature on lean applicability in the mining industry in Ghana. The paper seeks to explore variables, which may be considered in lean applicability and implementation in the mining industry on: principles that are identified with the lean strategies application; assess the various tools that are adopted for the lean implementation; determine how the lean management strategies are applied in the mining industry; explore the main benefits derived by the players in the mining industry for adopting lean strategies; and finally, identify the challenges that confront mining companies in their quest of adopting lean strategies. It is concluded that leanness as a management principle can successfully be applied to any sector of the economy. Base on such premise (postulation), it is worthy of mention that there is evidence of great advances regarding leanness as a management practice in the mining industry across the globe.